INVESTIGATING USER PREFERENCES FOR SMARTPHONE ICON DESIGN: A KANO MODEL ANALYSIS - Xia Bingying; Mat Redhuan Samsudin (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
In the ever-evolving realm of smartphone interface design, understanding user preferences is paramount. This study endeavors to comprehensively scrutinize such preferences utilizing the Kano model. Engaging 100 participants, the research assessed perceptions regarding 14 design attributes, employing a Likert scale for evaluations. Primary findings elucidated that attributes like recognizability, usability, personalization, and display effect hold paramount importance. However, an intriguing observation was a suggested potential variance across age demographics, which, upon further introspection, remained inconclusive in this research. This denotes an avenue necessitating future exploration. Designers, while conceptualizing smartphone interfaces, are advised to prioritize these identified attributes, possibly complementing age-specific needs, to ensure heightened user satisfaction. Ultimately, this research highlights the Kano model’s robustness and its invaluable contribution to the domain of smartphone interface design research.